The Effect of Corporate Governance and Company Size on Tax Avoidance - Ceacilia Srimindarti; Cici Andriani Widyaningsih; Rachmawati Meita Oktaviani; Pancawati Hardiningsih (Jurnal Organisasi dan Manajemen, 2022)
Purpose – This study aims to examine the effect of corporate governance and company size on tax avoidance in manufacturing companies. Methodology – The population includes all the manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019 and the 288 companies used as samples were selected through the purposive sampling method. A regression model was used for analysis. Findings – The results showed that institutional ownership, independent commissioners, and audit committee did not affect tax avoidance but managerial ownership and firm size have some influence. It was recommended that companies improve good governance by reducing their tax avoidance policies while other variables such as audit quality, executive character, liquidity, accounting conservatism, and capital intensity are suggested to be added to further studies related to tax avoidance. Originality – The novelty of this study is examine all corporate governance mechanisms consist of institutional ownership, independent commissioner, audit committee, and managerial share ownership on tax avoidance.